Longitudinal alterations of the gut mycobiota and microbiota on COVID-19 severity - Yuichi Maeda; Daisuke Motooka; Takahiro Kawasaki; Hiroya Oki; Yoshimi Noda; Yuichi Adachi; Takayuki Niitsu; Shota Okamoto; Kentaro Tanaka; Kiyoharu Fukushima; Saori Amiya; Reina Hara; et al. (BMC Infectious Diseases, 2022)
Abstract Background The impact of SARS-CoV-2 infection on the gut fungal (mycobiota) and bacterial (microbiota) communities has been elucidated individually. This study analyzed both gut mycobiota and microbiota and their correlation in the COVID-19 patients with severe and mild conditions and follow-up to monitor their alterations after recovery. Methods We analyzed the gut mycobiota and microbiota by bacterial 16S and fungal ITS1 metagenomic sequencing of 40 severe patients, 38 mild patients, and 30 healthy individuals and reanalyzed those of 10 patients with severe COVID-19 approximately 6 months after discharge. Results The mycobiota of the severe and mild groups showed lower diversity than the healthy group, and in some, characteristic patterns dominated by a single fungal species, Candida albicans, were detected. Lower microbial diversity in the severe group was observed, but no differences in its diversity or community structure were detected between the mild and healthy groups. The microbiota of the severe group was characterized by an increase in Enterococcus and Lactobacillus, and a decrease in Faecalibacterium and Bacteroides. The abundance of Candida was positively correlated with that of Enterococcus in patients with COVID-19. After the recovery of severe patients, alteration of the microbiota remained, but the mycobiota recovered its diversity comparable to that of mild and healthy groups. Conclusion In mild cases, the microbiota is stable during SARS-CoV-2 infection, but in severe cases, alterations persist for 6 months after recovery.